SUN-550 Pressor Refractory, Liothyronine Responsive Myxedema Cardiogenic Shock without Myxedema Coma - Willis, Cornelia (J Endocr Soc, 2019)
Introduction: Typical features of severe hypothyroidism include myxedema coma with or without associated cardiogenic shock which manifests as persistent hypotension, hypothermia, and hypoventilation in the setting of other typical features of myxedema coma to include confusion and swelling in the face and extremities. No prior reports of myxedema cardiogenic shock without other features of myxedema coma have been described. Treatment with liothyronine is controversial in the setting of severe hypothyroidism as it is associated with coronary artery disease and worse cardiovascular outcomes. This case report introduces a 66 year old male with subtle findings of myxedema cardiogenic shock without features of myxedema coma who remained on vasopressors until administration of liothyronine. Case Presentation: This is a 66 year old male with a history of hypertension, ischemic cardiomyopathy with an ejection fraction of 35%, right MCA stroke with residual hemiparesis, expressive aphasia, and dementia as well as primary hypothyroidism. Medications included telmisartan 40mg daily, atorvastatin 40mg daily, levothyroxine 0.125mg Monday-Friday, 0.25mg Saturday and Sunday, and valproic acid 250mg three times daily. He was brought to the emergency department after experiencing a 5 minute long witnessed tonic clonic seizure. Initial laboratory studies showed a mild leukocytosis with left shift, elevated lactate, TSH of 136.9, and an undetectable free T4 and valproic acid levels. Urine culture ultimately grew E. coli with negative blood cultures and the remainder of the workup was unremarkable. Admission vital signs showed a blood pressure of 107/70, heart rate 83, respiratory rate 15, and oxygenation 95% on 2L by nasal cannula. Physical exam only revealed a cachectic older male with baseline neurologic deficits to include orientation to person only. There were no features of myxedema or myxedema coma. IV fluids and antibiotics were started as well as 100mg IV hydrocortisone and 0.112 mg IV levothyroxine every 8 hours. The patient developed fluid refractory hypotension requiring ICU transfer for pressor support with vasopressin and norepinephrine without improvement of his MAPs. A bedside echocardiogram completed in the ICU showed a significantly reduced ejection fraction. After 12 hours of inability to maintain MAPs >65, he was started on 10mcg oral liothyronine every 8 hours. Within 4 hours of starting liothyronine pressors were successfully discontinued. Echocardiogram obtained after discontinuation of pressors showed an ejection fraction of 40%. Discussion: Pressor refractory shock with concomitant hypothyroidism should bring up concerns for myxedema cardiogenic shock, even without features of myxedema coma. In this patient with existing cardiomyopathy, liothyronine was successfully used to treat severe hypothyroidism without decrease in the patient’s ejection fraction.